DESAIN KEMASAN PRODUK KULINER TRADISIONAL KONJI ANAK LOBA INSTAN DALAM MENINGKATKAN BRANDING KAMPUNG ADAT KOTO SENTAJO - Zulmifta Huljannah; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
One of the potential attractions that support the development of tourist areas is typical food which can be souvenirs for tourists. Souvenirs are an important part of tourism promotion. One of the important elements of tourism promotion is branding. Branding is an effort to strengthen the value of a brand. If it is associated with a product, Branding can be applied to packaging so that it can add value to a product, so that it can attract consumer interest. When you know the steps for making a packaging design that can become an identity for the product and tourist area you want to promote, you will produce stages and conditions for how to design an attractive one. This can be started from understanding the current state and condition of the tourist area. Attractive packaging design is expected to be able to accommodate a message/communication between producers and consumers. The method used in this research is descriptive qualitative method. The result of this research is the design of this packaging design, the name "Konji Anak Loba Etek Typical Koto Sentajo Traditional Village". The packaging colors used are white, green, and yellow. This certainly means that this activity can help the community's economy. And it is hoped that it will be able to improve the Branding of the Koto Sentajo Traditional Village. Keywords: konji anak loba, instant, branding